2009
DOI: 10.1080/18811248.2007.9711575
|View full text |Cite
|
Sign up to set email alerts
|

LWR High Burn-Up Operation and MOX Introduction; Fuel Cycle Performance from the Viewpoint of Waste Management

Abstract: From the viewpoint of waste management, a quantitative evaluation of LWR nuclear fuel cycle system performance was carried out, considering both higher burn-up operation of UO 2 fuel coupled with the introduction of MOX fuel. A major parameter to quantify this performance is the number of high-level waste (HLW) glass units generated per GWd (gigawatt-day based on reactor thermal power generation before electrical conversion). This parameter was evaluated for each system up to a maximum burn-up of 70 GWd/THM (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Burn-up calculations for UO 2 fuels with 28, 45, and 70 GWd/THM (gigawatt days per ton of heavy metal) were conducted; enrichments of U-235 were chosen to be 2.6, 4.5, and 6.5 wt.%, respectively [4]. The Pu isotopic compositions in initial MOX fuels were calculated from the above UO 2 spent fuel compositions, assuming the cooling periods for UO 2 spent fuels were 4, 30, and 50 years and the storage periods for the MOX fuels before being loaded into a PWR were 2 and 10 years.…”
Section: Heat Generation Rate In Mox Spent Fuelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Burn-up calculations for UO 2 fuels with 28, 45, and 70 GWd/THM (gigawatt days per ton of heavy metal) were conducted; enrichments of U-235 were chosen to be 2.6, 4.5, and 6.5 wt.%, respectively [4]. The Pu isotopic compositions in initial MOX fuels were calculated from the above UO 2 spent fuel compositions, assuming the cooling periods for UO 2 spent fuels were 4, 30, and 50 years and the storage periods for the MOX fuels before being loaded into a PWR were 2 and 10 years.…”
Section: Heat Generation Rate In Mox Spent Fuelsmentioning
confidence: 99%
“…Our previous study demonstrated that the operation of a MOX-LWR increased the number of HLW glass units per GWd by a factor of two in comparison with that of a UO 2 -LWR due to the higher heat generation rate in the MOX HLW [4]. We have also determined the impact of wastes that include transuranic elements (hereafter referred to as TRU waste) on deep geological disposal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waste loading ratio of the conventional glass waste form for the LWR(non-PT) scenario has been determined by considering several constraints: 14) chemical solubility of waste element oxides in a glass matrix, solubility of molybdenum oxide (MoO 3 ), contents of PGMs in a waste form, maximum initial heat of 2.3 kW/package, and maximum heat of 0.35 kW/package after a 50-year storage. The …”
Section: Wastes From Fbr Fuel Cyclesmentioning
confidence: 99%
“…Both the noble metals and the yellow phase could cause problems with the disposal of high-burn-up UO 2 and MOX fuels. 3,4) The usage of MOX fuel is, inevitably, tied to spent fuel reprocessing. The resulting production of intermediate-level waste, including transuranic elements, is of concern from the viewpoint of waste management.…”
Section: Introductionmentioning
confidence: 99%